Ankyloglossia and lingual frenotomy in neonates: scoping review protocol (Research, Society and Development, 2023)
This article presents the scope review protocol on the methods of evaluating ankyloglossia in neonates submitted to frenotomy surgery in the last five years, focusing on diagnostic protocols for surgical intervention decision, postoperative results of lingual frenotomy and periods of proservation. The protocol aims to document the processes related to the planning and methodological conduct of an extension review of scope, guided by the guidelines of the Joanna Briggs Institute (JBI). The review protocol was prepared following the items of the PRISMA Extension for Scopings Reviews (PRISMA-ScR): Checklist and Explanation. The same was registered in the Open Science Framework.